Testing multi-factor asset pricing models in Borsa Istanbul - Özer, Gökhan; Yıldırım Kutbay, Aysegül (My University, 2022)
This study aims to test the validity of multi-factor asset pricing models on the portfolios of nonfinancial companies whose shares are traded on Borsa Istanbul and to identify the model with the best explanatory power. Accordingly, the relationships between annual book-to-market equity ratio, firm size, market portfolio return, return on capital, operating profitability, momentum and value-added intellectual coefficient between 2008-2019 were analyzed using panel data analysis. As a result of the analyses made, it has been observed that Fama French's three and five factors, Carhart (momentum), q-factor, and suggested models are successful in explaining the returns of portfolios formed by nonfinancial companies. Furthermore, according to the GRS-F test statistic, the q-factor model was found to have higher explanatory power than other models.
Keywords: İktisat; İşletme Finans